2014
DOI: 10.1063/1.4895069
|View full text |Cite
|
Sign up to set email alerts
|

Fluoropolymer coatings for improved carbon nanotube transistor device and circuit performance

Abstract: Articles you may be interested inHigh-performance carbon-nanotube-based complementary field-effect-transistors and integrated circuits with yttrium oxide Appl. Phys. Lett. 105, 063101 (2014); 10.1063/1.4892918High performance transistors via aligned polyfluorene-sorted carbon nanotubes Appl. Phys. Lett.We report on the marked improvements in key device characteristics of single walled carbon nanotube (SWCNT) field-effect transistors (FETs) by coating the active semiconductor with a fluoropolymer layer such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…[347] The difference between the intrinsic gate capacitance and the parallel-plate capacitance is more significant with lower SWCNT density or higher dielectric capacitance. [54,364] Preventing water adsorption and reducing dielectric trap states via the use of hydrophobic dielectrics, such as self-assembled nanodielectrics, [338,365] or encapsulation layers, such as AlO x [21,354] or fluoropolymers, [55,366] have proven to be effective approaches for realizing the reliable and stable operation of SWCNT FETs. [33] The on-state conductances and mobilities of selected solutionprocessed SWCNT FETs [36,43,132,155,165,207,208,213,214,236,257,296,297,338] versus channel length are shown in Figure 6F,G.…”
Section: Semiconducting Swcnt Networkmentioning
confidence: 99%
“…[347] The difference between the intrinsic gate capacitance and the parallel-plate capacitance is more significant with lower SWCNT density or higher dielectric capacitance. [54,364] Preventing water adsorption and reducing dielectric trap states via the use of hydrophobic dielectrics, such as self-assembled nanodielectrics, [338,365] or encapsulation layers, such as AlO x [21,354] or fluoropolymers, [55,366] have proven to be effective approaches for realizing the reliable and stable operation of SWCNT FETs. [33] The on-state conductances and mobilities of selected solutionprocessed SWCNT FETs [36,43,132,155,165,207,208,213,214,236,257,296,297,338] versus channel length are shown in Figure 6F,G.…”
Section: Semiconducting Swcnt Networkmentioning
confidence: 99%
“…This is believed to be due to the remaining oxygen to be strongly bonded to the defects and edges of the MoS2 channel [18]. Improvement in the off-current states upon coating with Teflon-AF is possibly due to the polar molecules of the fluoropolymer which will partially neutralize charged dopants [22,29]. Figure 4(b)).…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have shown that the performance variations of graphene and carbon nanotube (CNT) FETs can be reduced by applying a monolayer self-assembled hexamethyldisilazane (HMDS) layer between the back gate dielectric and the device channel or on the top surface of the device channels [18][19][20]. Other reports showed that passivating the surface of graphene and phosphorene FETs by a thicker hydrophobic film, such as fluoropolymers, results in more lasting positive changes and improved consistency in device to device performance [21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…During the past two decades, many different techniques have been developed to fabricate polymer tubes, such as the template method, self‐assembling method, electrostatic spinning method and so on . The coating of a fluoropolymer layer on single‐walled carbon nanotube field‐effect transistors was found to improve drastically the key device characteristics . However, fluoropolymer nano‐ and microtubes either formed from fluoropolymers or polymerized from fluoromonomers have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%